Kajian Teknis dan Biaya Kegiatan Rehandling Batubara PT Bukit Asam Tbk Tanjung Enim Sumatera Selatan - Rahmad Tanjung; Janiar Pitulima; Delita Ega Andini (MINERAL, 2021)
The East Block Muara Tiga Besar Utara mining system uses Shovel and Trucks where the digging stage uses excavators and bulldozers and the transport stage uses a dump truck. Coal production target of Muara Tiga Besar Utara Block Timur in July is 300,000 tons and August is 294,000 tons. The method used in this research is quantitative data analysis method by calculating the productivity of digging and transporting tools, analyzing the technical implementation of coal rehandling activities and analyzing the cost of coal production and rehandling activities. The results of this study obtained the productivity of PC 400 Lc excavator304.35 tons/hour, bulldozer D 375A of 674.61 tons/hour and Hino FM 320FI dump truck equipment of 37.06 tons/hour, the cost of coal production in July is IDR 13,772,009,648.00, in August IDR 13,495,592,315.10 and the cost of coal rehandling activities is IDR 160,685,158.30/month. Based on the cost of coal production and the cost of coal rehandling activities, it can be analyzed that there was a decrease in production costs between July and August due to a decrease in mining production targets in anticipation of coal rehandling activities.